Intercultural Citizenship in Indonesian EFL Higher Education: Exploring Students and Teachers’ Perception and Teaching Praxis - Deisyi Anna Batunan; Józef Trzebuniak (Universitas Pendidikan Ganesha, 2026)
Research into intercultural citizenship (IC) has emerged since the last decade, yet teachers’ and students’ perspectives towards IC construct and teachers’ teaching praxis to address IC have been surprisingly absent from this body of literature. This investigation was intended to fill this empirical lacuna. Drawing on a survey with both 100 students majoring in English education and 10 teaching staff from a state-owned university located in the eastern part of Indonesia and on a semi-structured interview with 10 students and 10 lecturers, the study focused on how teachers and students perceived IC construct and what action to take as an intercultural citizen and how teachers delivered IC-laden instruction in their daily teaching praxis. In particular, teachers' and students’ beliefs and experiences as well as teachers’ instructional strategies were explored. The data revealed that students and teachers had an impartial understanding of the IC construct. Furthermore, from the teachers’ side, this suboptimal understanding of IC dimensions, inter alia, communication, knowledge, and attitude, governed how teachers delivered incomprehensive IC-laden instruction and thus adversely influenced how students constructed their beliefs, even more so with the absence of civic action in teaching IC. As a pedagogical implication, the authors suggest how to incorporate IC into regular instruction at both theoretical and practical levels through specific designs of task, text, and test and through the empowerment of teachers’ professional development